The correction of the dimensionless equation for the mass transfer coefficient estimation during the membrane modules regeneration - Huliienko S. V.; Korniienko Y. M.; Metlina M. S.; Tereshenko I. Y.; Kaminskyi V. S. (Журнал інженерних наук)
The cleaning or regeneration of fouled membrane modules is an essential procedure in the membrane equipment operation. Despite the development of some successful cleaning techniques, the predictions of the membrane separation process operation parameters after regeneration is still an unsolved problem. In our previous works, the attempt to develop the methodology of estimating the membrane productivity after the regeneration of the fouled spiral wound membrane modules by cleaning the subatmospheric pressure has been made. However, this methodology requires some improvement, including the correction of the dimensionless equation to calculate the mass transfer coefficient. In this work, a set of additional experiments was carried out, and the corrections of the mass transfer correlation were done using both new and previously obtained experimental data. As a result, the improved dimensionless equation was contained as Sh = 0.00045Re0.8Sc0.33(de/l). This equation is valid in the range of Reynolds number variation of 0.4–60.0 for the case of the regeneration of spiral wound modules and can be used for the prediction of the permeate flux after the regeneration procedure.